Beyond Algorithmic Spirituality: An Islamic Ontological Framework for Digital Religious Practice - M. Febriyanto Firman Wijaya; Wahid Nur Tualeka; Mahmud Muhsinin; Ahmad Ghozi Al Afnan (Khazanah Theologia, 2025)
Purpose: This study aims to develop an Islamic ontological framework for digital religious practice as a response to the reductionism and fragmentation characterizing digital New Age spirituality. The research addresses a critical gap in contemporary scholarship, where digital spirituality is often examined descriptively or pragmatically without sufficient engagement with underlying ontological foundations, particularly within Islamic philosophical discourse. Methodology: This research employs a qualitative conceptual–philosophical approach using systematic conceptual synthesis. The study analyzes twenty-five peer-reviewed scholarly articles published between 2018 and 2025 on digital religiosity, New Age spirituality, and Islamic ontology, alongside classical Islamic sources. Following Jaakkola’s framework for conceptual research, the analysis proceeds through thematic categorization, comparative ontological analysis across six dimensions, and abductive theoretical synthesis to construct a normative framework of Islamic cyberspirituality. Findings: The study identifies four constitutive patterns of digital New Age spirituality—individualism, syncretism, aesthetic spirituality, and commodification—which collectively generate three ontological ruptures: displacement of transcendence by subjective emotionalism, replacement of religious authority by algorithmic validation, and transformation of spiritual discipline into consumable experience. In contrast, Islamic cyberspirituality is shown to rest on two interlocking principles: tawhid as the ontological axis preserving the Creator–creation distinction and revelation-based truth, and tazkiyah al-nafs as a transformative discipline orienting spiritual growth vertically toward God. This framework repositions technology as wasīlah (instrumental means) rather than ghāyah (end), and generates concrete implications across five domains: digital da‘wah, online Sufism, authority structures, attention governance, and religious identity formation. Implications: The findings offer actionable guidance for Muslim content creators, educators, religious institutions, technologists, and individual believers seeking to cultivate authentic digital spirituality. The framework provides evaluative criteria for digital religious content, ethical principles for technology design, and practical strategies for resisting commodification and algorithmic domination in religious practice. Originality/Value: This study contributes original value by moving beyond critique toward constructive ontological reconstruction. It is among the first to systematically integrate classical Islamic metaphysics with contemporary digital practice theory, demonstrating that tawhid and tazkiyah al-nafs provide robust conceptual resources for addressing algorithmic authority, attention commodification, and spiritual fragmentation in digital environments.